2016
DOI: 10.1002/jbm.b.33543
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a two-stage antibacterial hydrogel dressing for healing in an infected diabetic wound

Abstract: Various types of wound dressings have been used to treat complex infections in diabetes mellitus. This study is the first to evaluate the healing effects using a two-stage dressing in infected diabetic wounds. A two-stage antibacterial hydrogel dressing (two-stage dressing) was established with two time phases, an antibacterial phase and a drug release phase. We established each phase by using a swelling and rate of drug release test. These results suggested that the antimicrobial phase is activated as soon as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…It is believed that Ag rarely induces resistance due to the low cytotoxicity. Its safety threshold is wider than many other antimicrobial agents, reducing the risk of harmful side effects to humans [3, 12, 74]. AgNPs can be easily synthesized in various shapes and sizes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is believed that Ag rarely induces resistance due to the low cytotoxicity. Its safety threshold is wider than many other antimicrobial agents, reducing the risk of harmful side effects to humans [3, 12, 74]. AgNPs can be easily synthesized in various shapes and sizes.…”
Section: Resultsmentioning
confidence: 99%
“…A two‐stage dressing (two times of antibacterial phase and drug release phase) of CMC, nano‐Ag, polyacrylic acid sodium (PAAS), and Calculus bovis was evaluated on S. aureus ‐infected diabetic wounds and showed a significantly higher wound closure rate. In vivo testing proved the advantages of sustained drug release, rapid antibacterial activity, and improved wound healing by complete closure at day 14 for two‐stage dressing [3].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Drug release experiments showed that the antibacterial phase occurred earlier than the long-duration drug release phase. Thus, the drug-loading system achieved rapid anti-infection, continuous reduction of inflammatory response, and accelerated healing of S. aureus-infected wounds (He et al, 2017).…”
Section: Anti-infectionmentioning
confidence: 99%